PREDICTING SOIL WATER CONTENTS UNDER SEMI-ARID CLIMATE - Khalid Ahmed; Ahmed Saeed; Ghazwan Dahham; Mahmoud Rafik (Mesopotamia Journal of Agriculture)
One of the world’s critical challenges is the optimal use of water resources for agricultural production. Groundwater scarcity in semiarid conditions and still using traditional tillage systems without prior knowledge affect these tools on water consumption, tillage practices change many soil properties one of its void spaces which plays a significant role in the ability of soil water content, so the aim of this paper to study the effect of tillage methods on soil water content throughout growing season. The experiment included using Traditional Tillage methods (chisel, vertical disc, moldboard plow) and irrigation time (after tillage, after germination, after final irrigation) under two types of irrigation systems (Semi-solid system and center pivots). The data was analyzed by using the Design Expert program and the results showed a significant effect for type of irrigation system and soil tillage system in soil water content. The soil moisture content starts to increase gradually in all tillage methods until the end of the growing season and reaches to 20.14% in 20 cm depth after the final irrigation stages of the growing, soil water content depends on the type of plowing methods which reflects the way manipulation of the soil layers and as a result facilitate water irrigation to penetrate soil layers, some treatment recorded (21.04%) and other recorded (19.13%). The predicting models show significant differences with acceptable accuracy in predicting soil humidity in the growing season.